Gone girl : a novel - Flynn, Gillian, 1971- (Crown, 2012)
On the morning of his fifth wedding anniversary, Nick's wife Amy suddenly disappears. The police immediately suspect Nick. Amy's friends reveal that she was afraid of him, that she kept secrets from him. He swears it isn't true. A police examination of his computer shows strange searches. He says they aren't his. And then there are the persistent calls on his mobile phone. So what really did happen to Nick's beautiful wife?